Wanted dead or alive? The tradeoff between in-vivo versus ex-vivo MR brain imaging in the mouse - Lerch, Jason P.; Gazdzinski, Lisa; Germann, Jurgen; Sled, John G.; Henkelman, R. Mark; Nieman, Brian J. (Frontiers in Neuroinformatics, 2012)
High resolution MRI of the mouse brain is gaining prominence in estimating changes in neuroanatomy over time to understand both normal developmental as well as disease processes and mechanisms. These types of experiments, where a change in time is to be captured as accurately as possible using imaging, face multiple experimental design choices. Chief amongst these choices is whether to image ex-vivo, where superior resolution and contrast are available, or in-vivo, where resolution and contrast are lower but the animal can be followed longitudinally. Here we explore this tradeoff by first estimating the sources of variability in anatomical mouse MRI and then, using statistical simulations, provide power analyses of these experiment design choices.